CHILDREN ASTHMA CONTROL TEST IS A MODERN APPRAISAL TOOL TO CHECK THE CONTROL OVER BRONCHIAL ASTHMA AMONG CHILDREN, CORRESPONDING TO THE NEW GINA 2006 CONCEPT - L.M. Ogorodova; E.L. Timoshina (Union of pediatricians of Russia, 2006)
The article gives data on the effectiveness of bronchial asthma treatment among children in the world according to the findings of the epidemiologic research. It shows that among most children with asthma there is no control over the disease, which is somehow related to the insufficient implementation level of Gina recommendations and absence of adequate basic therapy. In the article, the authors give a definition to the term «asthma control». They also highlight the main findings of goal research and the meaning of correct objective selection for the treatment. For the first time, the article provides the information on the new tool for childhood asthma control certified by Gina - childhood asthma control test.Key words: bronchial asthma, children, treatment, Gina, childhood asthma control test.